Ethical infractions committed by nursing professionals received by the nursing ethics committee: integrative review - Martinez, William Donegá; Bonifácio, Neuza Alves [UNESP]; Michelin, Aparecida de Fátima [UNESP]; Sakamoto, Sabrina Ramires [UNESP]; Faria, Josimerci Ittavo Lamana; André, Júlio César (Acta Paulista de Enfermagem, 2024)
Objective: To identify, analyze, and characterize the incidents committed by nursing professionals received by the Nursing Ethics Committee. Methods: Integrative review conducted according to the methodology defined by the Manual for Evidence Synthesis from the Joanna Briggs Institute and registered on the Open Science Framework platform. Databases searched: Cumulative Index to Nursing and Allied Health Literature (CINAHL), Medical Literature Analysis and Retrieval System Online (MEDLINE via PubMed®), Web of Science, SciVerse Scopus (SCOPUS), Latin American and Caribbean Literature in Health Sciences (LILACS) and Nursing Database (BDENF) via Virtual Health Library (VHL). Studies entirely published in Portuguese, English, or Spanish (2018-2023) were included. Data management was carried out with Rayyan®. Results: A growing interest in infractions in complaints attributed to nursing professionals, which were accepted by the Nursing Ethics Committee in the professional context of the health area and expressed by predominant publications in the last five years, was verified. Conclusion: Mid-level professionals were the most reported, with a greater participation of Nursing Assistants. Negligence and Illegal Exercise of Profession were the criminal types of ethical infractions with the highest incidence. Nursing Ethics Committees, followed by victims’ families, Regional Nursing Councils, victims, and nurses were the main categories of complainants of ethical violations. Verbal Warning was the most prevalent type of penalty applied.
Infracciones éticas cometidas por profesionales de enfermería admitidas por la Comisión de Ética de Enfermería: revisión integradora
Infrações éticas cometidas por profissionais de enfermagem acolhidas pela comissão de ética de enfermagem: revisão integrativa
Keywords: Brazil; Ethics committees; Ethics, nursing; Legal process; Nurse practitioners